THE IMPACT OF INVESTMENT MECHANISMS ON THE DEVELOPMENT OF ELECTRIC NETWORKS - Sobirov, Muzaffar Azatovich (INTERNATIONAL CONFERENCES, 2023)
In this article, the need for the problem of forming a strategy for re-equipment of the electrical network complex is considered. Creating technologically and economically efficient power supply systems leads to the need to find an optimal plan.